Nutritional Status, Dust Exposure and Risk Factors for Acute Respiratory Infections for Workers in Industrial Estates - Ichayuen Avianty1 , Fakhrurradhi Luthfi2 , Suharto3 , Nanda Novziransyah4 , Kipa Jundapri3 , Rubi Gi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acute Respiratory Infections (ARI) are a health problem that has not been handled properly in Indonesia,every year the incidence of acute respiratory infections is still high, which can be fatal, namely death. Severalfactors cause acute respiratory infections such as nutritional status, dust exposure, length of exposure todust, and years of service for workers in industries who have a high risk of acute respiratory tract infectionproblems. This study aims to determine the risk factors for acute respiratory infections in the industry. Thisstudy uses a cross-sectional approach with a sample of 89 respondents, where the results will be analyzedusing the chi-square test. The result of this study is that there is a relationship between nutritional status,dusty workspace, length of exposure to dust, and length of work with the incidence of acute respiratoryinfections in industrial workers. Based on the results of this study, it is hoped that workers and the industrywill pay attention to the use of PPE to minimize dust exposure to workers in the industry.